Comparative Clinical Study Between Modified Ureteral Orthotopic Reimplantation and Cohen Method Under Pneumovesicum in Pediatric Patients With Hydroureteronephrosis - Chang, Jiaming; Zhang, Qiangye; Hou, Peimin; Wang, Dongming; Li, Aiwu; Lv, Xiaona (Frontiers in Pediatrics, 2020)
Abstract Purpose: To report our initial experience of a modified ureteral orthotopic reimplantation technique under pneumovesicum and compare the outcome of our technique versus Cohen technique under pneumovesicum for correcting primary obstructive megaureter(POM) or vesicoureteral reflux(VUR) in pediatric patients. Methods: 46 patients (38 POM and 8 VUR, mean age 16.24 months) treated with modified ureteral orthotopic reimplantation (OR group) and 43 patients (34 POM and 9 VUR, mean age 22.98 months) treated with the Cohen reimplantation (CR group) under pneumovesicum. We compared the results in patients' perioperative and follow-up conditions. Results: The mean operative time was significantly shorter in OR group(OR:86.86 and 108.18 for unilateral and bilateral versus CR:95.14 and 124.29, min). The mean postoperative hospital stay(OR: 5.02 versus CR:5.07, day), blood loss(OR:3.67 and versus CR:3.84, ml) and follow-up time(OR:POM 23.17 versus CR:23.37, month)had no significant difference between two groups. There was one patient converted to open surgery in CR group and no conversion in OR group. Postoperative febrile urinary tract infection(UTI) occurred in 2 cases in each group, all controlled by antibiotics. All patients in two groups showed improved hydroureteronephrosis and all VUR patients showed reflux resolution post surgery. Conclusions: Our modified ureteral orthotopic reimplantation technique under pneumovesicum can be performed safely and effectively, achieving a high success rate that is equivalent to Cohen technique under pneumovesicum but with simpler procedure and shorter operation time.